2019
DOI: 10.1080/13880209.2019.1688843
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin alleviates diabetic nephropathy via inhibiting podocyte mesenchymal transdifferentiation and inducing autophagy in rats and MPC5 cells

Abstract: Context: Curcumin could ameliorate diabetic nephropathy (DN), but the mechanism remains unclear.Objective: The efficacy of curcumin on epithelial-to-mesenchymal transition (EMT) of podocyte and autophagy in vivo and in vitro was explored.Materials and methods: Thirty male Sprague–Dawley rats were divided into the normal, model and curcumin (300 mg/kg/d, i.g., for 8 weeks) groups. Rats received streptozotocin (50 mg/kg, i.p.) and high-fat-sugar diet to induce DN. Biochemical indicators and histomorphology of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 25 publications
(28 reference statements)
6
49
0
Order By: Relevance
“…Increased formation of autophagosomes observed in vitro also confirmed autophagic disorder in this study. These findings are consistent with those reported by previous studies [ 21 , 22 ]. Resveratrol and genistein intervention increase the expression of LC3-II, reduce the expression of p62, activate autophagy, and promote podocyte repair in vitro [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 94%
“…Increased formation of autophagosomes observed in vitro also confirmed autophagic disorder in this study. These findings are consistent with those reported by previous studies [ 21 , 22 ]. Resveratrol and genistein intervention increase the expression of LC3-II, reduce the expression of p62, activate autophagy, and promote podocyte repair in vitro [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 94%
“…Impaired autophagy activity contributes to the pathogenesis of DN, and the recovery of autophagy activity may be a promising therapeutic target for DN. Currently, the latest studies have confirmed that the inhibition of PI3K/Akt/mTOR signaling pathway restored autophagy and ameliorate DN (Tu et al, 2019 ; Wang et al, 2019 ). Result showed that the phosphorylation levels of PI3K, Akt, and mTOR in diabetic rats and mesangial cells induced by high glucose were obviously decreased by icariin treatment.…”
Section: Discussionmentioning
confidence: 95%
“…The most common clinical feature of DN is progressive proteinuria due to impairment of the GFB, and the normal morphology and function of podocytes play an important role in proteinuria formation and maintenance of renal function [ 14 , 15 ]. In many studies, podocytes have been treated with high glucose to cause DN in experimental models [ 16 , 17 ]. In this study, we treated podocytes with high glucose to construct a cell model of DN, and found that high glucose induced increased levels of inflammation and cell damage in podocytes.…”
Section: Discussionmentioning
confidence: 99%